Resistant pests : A producer’s perspective - McPhee, G. (Phytoprotection, 1994)
The world population continues to grow rapidly while also demanding a safe, secure food supply. This supply is produced on a limited soil and water base which needs to be protected today and for future generations. By adapting to the control methods that are being used, current and new pests are changing and thriving under the conditions we provide while we produce food. A resource efficient and sustainable food production chain requires that producers of crops and livestock have a selection of safe, effective tools to manage pests to acceptable levels, and to minimize their ability to adapt. At present, the problem exists that those with responsibility for pest management like government policy makers, government regulators, the pest control industry, research and expert committees, food producers and consumers, lack a long-term strategic plan on how to manage pests safely and effectively. Such a strategic plan would clearly identify effective pest management as a major key, one that would give food producers the means of providing for food security while maintaining soil quality and wildlife habitat. Because of the speed at which pest resistance or adaptation is occurring, the process of developing the long-term strategy must be put in place quickly.